Association between severe retinopathy of prematurity and postnatal weight gain in very low-birthweight infants at Chiang Mai University Hospital, Thailand. (2nd April 2020) - Wongnophirun, Ananya; Khuwuthyakorn, Varangthip; Tantiprabha, Watcharee; Wiwatwongwana, Atchareeya
ABSTRACT: Background : Poor postnatal weight gain has been associated with low serum IGF-1, a key factor in the pathogenesis of retinopathy of prematurity (ROP). Aim : To investigate an association between relative weight gain (RWG) and severe ROP in very low-birthweight (VLBW) Thai infants. Methods : The medical records of VLBW infants who were admitted to the neonatal intensive care unit in Chiang Mai University Hospital from June 2014 to December 2016 and screened for ROP were reviewed. RWG and total calorie intake (TCI) in the 2nd, 4rth and 6th week of age were calculated and those with no ROP/mild ROP and severe ROP requiring laser treatment were compared. Results : The study included 139 VLBW infants, 24 (17.3%) of whom had ROP requiring laser treatment. Infants with severe ROP requiring laser treatment had a lower median birthweight (840 vs 1, 195 g, p < 0.001) and median gestational age (GA) (27 vs 30 wk, p < 0.001) than those with no ROP/mild ROP. When RWG and TCI were compared, the infants with severe ROP requiring laser treatment had a lower RWG at the 2nd ( p < 0.01) and 4th weeks of age ( p < 0.05) and had a lower TCI at the 2nd week of age ( p < 0.001) than those with no ROP/mild ROP. Multivariate logistic analysis demonstrated that GA <29.5 w ( p < 0.01), hypotension ( p < 0.05), RWG <2.9 g/kg/d ( p < 0.05) and TCI <98.5 kcal/kg/day ( p < 0.001) at the 2nd week of age were independent risk factors for severe ROP requiring laser treatment. Conclusions : Poor weight gain and low calorie intake at the 2nd week of age were associated with severe ROP requiring laser treatment in VLBW infants. Monitoring weight gain and calorie intake during this period are essential and may improve the outcome of ROP. Abbreviations : BPD, bronchopulmonary dysplasia; IVH, intraventricular haemorrhage; NEC, necrotising enterocolitis; PDA, patent ductus arteriosus; PRC, packed red cells; PVL, periventricular leucomalacia; RDS, respiratory distress syndrome; ROP, retinopathy of prematurity; RWG, relative weight gain; SGA, small for gestational age; TCI, total calorie intake; VLBW, very low birthweight.